2018
DOI: 10.1136/bmjopen-2018-022220
|View full text |Cite
|
Sign up to set email alerts
|

Reduced prevalence of small-for-gestational-age and preterm birth for women of low socioeconomic position: a population-based cohort study comparing antenatal midwifery and physician models of care

Abstract: ObjectiveOur aim was to investigate if antenatal midwifery care was associated with lower odds of small-for-gestational-age (SGA) birth, preterm birth (PTB) or low birth weight (LBW) compared with general practitioner (GP) or obstetrician (OB) models of care for women of low socioeconomic position.SettingThis population-level, retrospective cohort study used province-wide maternity, medical billing and demographic data from British Columbia, Canada.ParticipantsOur study included 57 872 pregnant women, with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 22 publications
0
28
0
2
Order By: Relevance
“…Since data suggest that institutional racism is a contributing factor, place of birth, or model of maternity care, may also modulate these outcomes [ 41 ]. A recent population-level analysis in Canada described associations between midwifery care of at-risk populations and significantly reduced incidence of pre-term birth, low birth weight, and other adverse outcomes [ 54 ]. In our study, lower MISS scores were associated with significantly higher rates of neonatal mortality among Hispanic, black and white babies when examining race-specific outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Since data suggest that institutional racism is a contributing factor, place of birth, or model of maternity care, may also modulate these outcomes [ 41 ]. A recent population-level analysis in Canada described associations between midwifery care of at-risk populations and significantly reduced incidence of pre-term birth, low birth weight, and other adverse outcomes [ 54 ]. In our study, lower MISS scores were associated with significantly higher rates of neonatal mortality among Hispanic, black and white babies when examining race-specific outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In high resource countries, pregnant people who are recent immigrants, Indigenous, and/or disenfranchised by their lower socioeconomic status, race/ethnicity, incarceration, substance dependence, or housing instability have been reported to be at increased risk for poor health outcomes, and reduced access to high quality care [1822]. Few investigators have examined whether experiences of RMC differ by sociodemographic factors, but one U.S. national study identified racial disparities in the treatment of childbearing women in hospitals [23].…”
Section: Introductionmentioning
confidence: 99%
“…This midwifery-led continuity model is often promoted as the gold standard for maternity care for low risk women [14] who report fewer interventions and higher satisfaction than with other models such as medical-led or shared care [15]. It is also touted as a major contributor to the reduction of inequity [16, 17], even so, maternal health inequity persists in outcomes, care processes, and women’s experience within the New Zealand health system.…”
Section: Introductionmentioning
confidence: 99%